Bsf Maggot Cultivation Technology as an Alternative Fish Fish Feed in Kualu Village, Pekanbaru City, Riau Province - Nurul Aulia; Rosalimah Rosalimah; Rahmat Tillah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Organic material waste such as household waste and markets are widely available in the Pekanbaru City community and in environmental management public knowledge about the use of organic waste is still limited. The community of breeders and cultivators in Pekanbaru City also faces the increasing price of duck and fish feed, making farmers have to look for other alternatives to reduce feed costs. Cultivation of Maggot BSF is the right solution to overcome the problem. In this National Waste Care Day (HPSN) carried out assistance activities for BSF Maggot cultivation as an alternative to duck and fish feed which was carried out in Pekanbaru City, Panam. The method used in this activity is participatory training in lectures, discussions and BSF Maggot cultivation practices. The result of this training is the availability of Maggot BSF as a material for making duck and fish feed and the understanding, knowledge and skills of participants in the cultivation of Maggot BSF. The result of this activity was the enthusiasm of the community for the training as evidenced by the active participation of the community from beginning to end and the number of participants who were active in discussion and question and answer sessions. So it can be concluded that the training and practice of BSF Maggot cultivation in Pekanbaru City, Tampan was successful and increased the understanding and attitude of participants about the importance of processing organic waste waste and as an alternative to duck and fish feed ingredients.